Political Education Law Determination of Political Parties in Indonesia - Feridiansyah, Adham; Darkhan, Azamat (Alauddin Law Development Journal (ALDEV), 2024)
The political party system in Indonesia often causes confusion among the local populace, as political parties are the primary actors in a democratic society. Political participation is crucial for a substantive democracy state, and the public needs to understand the importance of political parties through political education. Two main concerns are designing an ideal political education model to encourage political participation and reconciling with parties that do not engage in political education. The study suggests discussing a political education model for the public and promoting campaigns to encourage political parties to provide political education. The results of political parties should be evaluated through the efforts of the BPK and inspectorates, and their results should be made publicly available. The article is written using first- and second-class legal materials, using the method of defiance known